O ensino da dança: fatores do movimento de Rudolf Laban na perspectiva da educação personalizada de Víctor García Hoz - SANTOS, Alyce Clara Cardoso dos (2024)
This article is about the teaching of dance, more precisely Rudolf Laban's movement factors: fluency, space, weight and time, inserted into the perspective of Personalized Education at Colégio Mirante, a proposal that I learned about in August 2022 when I started an internship in the extracurricular activity of Jazz at the aforementioned private school, being the first institution in the country to approach this model, in 2020.The aim is to present personalized as an educational proposal, as well as to propose activities that integrate dance, the principles and pillars of personalized education. The research carried out was qualitative, with a bibliographic survey and the data collection procedures were free interviews with three teachers from Colégio Mirante and experiences lived in the internship at that school, which began in August 2022 and continues until the publication of this work in Ballet and Jazz classes. Throughout the study, we realized that personalized education is a pedagogical conception that acts in the integral development of the student and can be inserted in the context of dance teaching, which goes beyond the physical domain and goes through the cognitive, socio-affective, volitional and transcendental domains, in addition to helping in the process of acquiring autonomy, freedom, creativity, singularity, openness and communication. The main theoretical references are: Hoz (1970), Júnior E Lebiam (2021), Mota (2012), Macedo (2016), Rengel et al. (2017) and the Colégios de Fomento Education Model, translated by Solar Colégios. This article is presented as a course completion work in accordance with the Federal University of Pará's flexibilization standard in Normative Instruction No. 01/2023 - PROEG/UFPA.